Effects of Self-Disclosure on Attitudes Toward Seeking Professional Psychological Help Among Black Males - Grandy, Jody C (East Carolina University)
Black American males reported sadness and hopelessness and that everything takes an effort at a higher rate than Black women, Caucasian males, and other groups. Although the statistics related to Black males' depression are high, their attitudes toward seeking professional psychological help remain unfavorable. Black males are often grounded and socialized in traditional masculinity and ethnic ideologies, including those that prevent professional psychological care, a normative method of coping with distress. As men, they are socialized not to self-disclose their feelings, and as Black Americans, they learn the importance of social support within the Black community.
Keywords: Black males; Attitudes toward help-seeking; Self-disclosure; social support; Psychosocial Intervention; Disclosure; Humans; Male